The Holocene transgression in the Bohai Sea: insights from multi-proxy sedimentary records - Lichao Tang; Ya Ping Wang; Yuanfu Yue; Wei Feng; Fu Wang; Cong-Qiang Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Design of dual-function soil amendment via co-roasting K-feldspar with soda residue and oyster shell for acidity amelioration and potassium supply - Ernest Uwiringiyimana; Ren-Yong Shi; Jiu-Yu Li; Jia-Ning Gao; Yong-Ming Fu; Md. Romel Biswash; Cong-Ming Wu; Ren-Kou Xu (Journal of Environmental Chemical Engineering, 2026)

Window-specific effects of ultraviolet radiation and air pollution on ovarian reserve in infertile women: A retrospective cohort study - Qi Tang; Cong Fu; Hongyu Du; Qing Liu; Kui Yang; Zhuoni Xiao; Yanqing Xu (Environmental Pollution, 2026)

Synergistic alkaline etching and nitrogen lattice occupation strategy enables gradient defluorinated cathode for high-performance Li/CFx batteries - Hongwei Cai; Xiaoxiao Pan; Cong Li; Hao Luo; Menghan Lin; Mingyi Shang; Jiqiong Lian; Yanan Fu; Hongjun Yue; Huixin Chen; Xiaolong Li; Yujin Tong; et al. (Chemical Engineering Journal, 2026)

Modeling the motion and evaporation of a single spherical humidification droplet under hypobaric and extremely dry conditions - Jiale Hu; Yingying Wang; Zhiguo Fu; Dengjia Wang; Cong Song; Baimu Suolang; Pu Bai (Building and Environment, 2026)

Spatial heterogeneity and prioritization of chemical mixtures along the Yarlung Tsangpo River - Cong Wang; Xiaoping Wang; Wenyuan Su; Bao Zhu; Jie Fu; Kai Huang; Huimin Yu; Shuping Yang; Suona Zhuoga; Jianjie Fu (Water Research, 2026)

Propylparaben exposure may impair uterine decidualization via FDX1 downregulation and induce preeclampsia-like symptoms in mice - Xiaohui Li; Rui Fu; Huiyu Liu; Yuhan Cai; Cong Zhang (Reproductive Toxicology, 2026)

Crop rotations modulate chemical transformation of dissolved organic matter during mineral surface-bound Fe(II) oxidation in paddy soils - Cong Wu; Fangling Li; Taoyuan Ouyang; Wei Peng; Yanqi Xiao; Fu Liu; Qihong Zhu; Na Zhang; Hao-Jie Cui; Wenjuan Liao (Applied Geochemistry, 2026)

Protector or provocateur? Analysis of U.S. overseas military bases and terrorism - Ming Yan; Cong Fu; Hongyu Du; Deirdre Conlon; Shuang Zhao; Ruidun Chen; Silas Nogueira de Melo; Yuchen Li; Yanqing Xu (Applied Geography, 2026)

Deep learning-based shipborne sea-ice segmentation for ice-channel perception during Arctic convoy operations - Shouwen Li; Jiahui Fu; Lixuan Han; Cong Liu; Mingyang Zhang; Hongdong Wang (Ocean Engineering, 2026)

Unveiling the dynamic electron transfer at asymmetric Fe-O-Co sites for sustained PMS activation via in-situ synchrotron spectroscopy - Xian-Chuan Chen; Fu-Sheng Sun; Cong-Qiang Liu; Guang-Hui Yu (Journal of Environmental Sciences, 2026)

Reversible dual-mode responsive hydrogels with photo-triggered ring opening/closing and supramolecular assembly for erasable and reprogrammable information encryption and anti-counterfeiting - Dingkun Wang; Yaqi Zhang; Zhenhao Zhang; Hailong Yang; Yang Cong; Jun Fu (Chemical Engineering Journal, 2026)

Alkanoyl imidazoles from a marine-derived Nocardiopsis species: anomalous NMR behavior and antibacterial activity conferred by N-alkylation - Chao Gao; Cong Wang; Hui Luo; Zhi Liu; Shupeng Yin; Weiming Zhu; Peng Fu (Marine Life Science & Technology, 2026)

Revolution in plant breeding: From field to factory - Junjie Fu; Cong Tan; Xingping Zhang; Liang Li; Zonggeng Li; Jianan Zhang; Junhui Wang; Huan Liu; Qichang Yang; Richard G.F. Visser; Yunbi Xu (Molecular Plant, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Evaluation and comparison of TCR repertoire differences between patients with cervical cancer and healthy individuals - Wenwen Gao; Cong Wang; Jiawen Jia; Yiqian Li; Ting Li; Ling Liu; Yi Zhang; Haibin Yu; Cuiping Yang; Xiaoli Fu; Yongbin Chen; Yan Cheng (Science China Life Sciences, 2026)

Autotetraploid induction and one-step regeneration, and transcriptomic analysis in Dendrobium officinale - Cong-Dan Zheng; Jun-Yu Su; Shang-Yan Fu; Jie-Mei Deng; Zi-Ting Zhu; Heng-Yu Huang; Yuan-Zhong Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Effects of dietary Portulaca oleracea L. aqueous extract on growth performance, intestinal health and intestinal microflora of common carp (Cyprinus carpio) - Jing-Tong Huang; Cong-Fu Liu; Yu-Shi Cai; Li-Fang Li; Hai-Tao Zhao; Yan-Ping Yang; Rui-Fang Wang (Animal Feed Science and Technology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Rational design of carbon dots with pyrrole rings for visible in vitro diagnosis of vulnerable atherosclerotic plaque - Xuelian Wang; Wanting Fu; Minye Ji; Jian Zhang; Jia Qi; Junli Zuo; Ying Chen; Yan He; Qingwen Gu; Hong Wu; Zhilei Cong; Jinping Li; et al. (Chemical Engineering Journal, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

RlTTG1 isolated from Rosa laevigata Michx. regulates trichome development and stress response in transgenic Arabidopsis - Sinian Wu; Lisha Song; Yixi Chen; Cong Luo; Lingyun Wan; Guojian Liao; Wenjing Liang; Shugen Wei; Cuihong Yang; Yujian Huang; Ying Wei; Shixin Feng; et al. (Plant Science, 2026)

Effect of the combination of lactic acid, ε-poly-L-lysine and sodium isoascorbate on the swelling, microbiomics variation, and quality attributes of vacuum-packed fresh cut lotus root - Jiahui Jiang; Qianlong Shi; Dan Li; Qingmin Chen; Cong Han; Jing Wei; Maorun Fu; Huaimei Cao; Xiaofei Xin (Postharvest Biology and Technology, 2026)

Accelerated degradation of antibiotics via UV irradiation in the presence of chlorite: roles of reactive species, degradation pathways, and toxicity - Yu-qiong Gao; Xue-ting Ren; Yang-yang Liu; Ju-xiang Chen; Fu-xiang Tian; Nai-yun Gao; Cong Li (Journal of Water Process Engineering, 2026)

Unpacking asthma risks: A multi-level spatial analysis of social determinants of health in the U.S. - Ming Yan; Cong Fu; Xiao Huang; Siqin Wang; Yuchen Li; Lambed Tatah; Rui Zhu; Yanqing Xu (Applied Geography, 2026)

Immune-activated & pathology-characterized: the distinct clear cell renal cell carcinoma subtypes for 3PM strategies derived from artificial intelligence in multi-omics - Cong Zhang; Haijiao Zeng; Xinjing Liu; Guichuan Lai; Kangjie Li; Haitao Fu; Biao Xie; Xiaoni Zhong (EPMA Journal, 2026)

Advanced liquid metal interfaces: engineering embodied cognition in closed-loop human-machine ecosystems - Wenqi Wang; Jun Yang; Boya Song; Zhouyang Hu; Fangqing Wang; Sanwei Hao; Changyou Shao; Peng Fu; Hailin Cong; Caofeng Pan (Science Bulletin, 2026)

Aridity mediates the scale-dependent relationship between plant diversity and soil multifunctionality - Kai Wang; Cong Wang; Bojie Fu; Josep Peñuelas; Jordi Sardans; Arthur Gessler; Marcus Schaub; Xiaoming Feng; Yihe Lü; Zongshan Li; Wei Jiang; Mai-He Li (Journal of Environmental Management, 2026)

Synergistic effects of high temperature and hypoxia on energy metabolism and physiological homeostasis in the Chinese mitten crab (Eriocheir sinensis) - Cong Zhang; Dunqian Deng; Huixia Feng; Su Jiang; Zihao Song; Kai Zhang; Longlong Fu; Shaowu Yin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Bioinspired optical/electrical dual-modal flexible strain sensor with microcrack structure based on fluorescent hydrogel - Dingkun Wang; Guoqi Chen; Canjie Zhu; Jiayuan Ren; Yang Cong; Hailong Yang; Jun Fu (Chemical Engineering Journal, 2026)

Identification and spatiotemporal analysis of braided rivers in the Yarlung Tsangpo basin using an enhanced U-Net approach - Xiangyang Luo; Ying Lu; Bibo Zhang; Yadan Yang; Jiaxin Li; Wanying Fu; Xinke Bu; Cong Li (Journal of Hydrology, 2026)

Bioinspired iron porphyrin covalent organic framework nanozyme with peroxidase-like activity for ratiometric colorimetric and portable swab-assisted detection of nitrite in food samples - Jin Liu; Qiuyu Chen; Xiaoyan Meng; Cong Hu; Fengfu Fu; Zian Lin (Food Chemistry, 2026)

Photo–biodegradation drives organic matter-mediated carbon–nitrogen–sulfur cycling in the reservoir's surface-layer: A multi-index analysis - Haoyang Wang; Xinyu Lao; Khan M.G. Mostofa; Si-Liang Li; Cong-Qiang Liu; Jie Yuan; Jie Zhang; Fu-Jun Yue (Environmental Research, 2026)

Systematic monitoring model for zonal deformation of ultra-high arch dams driven by second-order idiosyncratic graph structures - Enhua Cao; Jianfeng Xue; Yangjia Li; Haotian Chang; Zhaoqing Fu; Cong Hu; Rongyao Yuan; Yangtao Li; Shaopei Hu; Tengfei Bao (Engineering Structures, 2026)

Proton and water migration regulation drives high-efficiency sulfuric acid concentration via ladder electrodialysis - Ziang Jia; Cong Liu; Ming Tan; Fei Liu; Wei Cong; Rongqiang Fu; Yang Liu; Yang Zhang (Desalination, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Revealing the overlooking role of polysulfides in sulfide-based denitrification biofilms through mathematical modeling - Yan Yang; Yu Liu; Cong Fan; Huimin Fu; Mohamed S. Mahmoud; Kang Dan; Hongxiang Chai (Bioresource Technology, 2026)

From bioprocess to market: Optimizing medium-chain carboxylate extraction for application readiness - Yiran Zhang; Aijie Wang; Yilu Sun; Xuening Zhang; Jianfeng Liu; Wen Wang; Cong Huang; Shaoping Fu; Honggang Deng; Yongping Shan; Jiadong Yu; Xufeng Yuan; et al. (Bioresource Technology, 2026)

Impact of deposition morphology on critical heat flux during pool boiling from horizontal tubes - Xiaowen Wang; Maolong Liu; Junlong Li; Junsen Fu; Xu Yan; Hongkang Tian; Tenlong Cong; Yao Xiao; Hanyang Gu (Annals of Nuclear Energy, 2026)

Experimental and numerical investigation on the dynamic response of a 15 MW semisubmersible floating offshore wind turbine including 1-mooring line failure scenario - Ikjae Lee; Da Li; Shenglei Fu; Cong Yi; Moohyun Kim; Alex Ran; Tuanjie Liu (Ocean Engineering, 2026)

Green extraction of undenatured type II collagen from goat cartilage by deep eutectic solvents: An integrated in silico and experimental study - Wei Wu; Yuhao Zhou; Jingjie Tan; Cong Wang; Mohammed Gagaoua; Rotimi E. Aluko; Zhongquan Zhao; Yongju Zhao; Yu Fu (Innovative Food Science & Emerging Technologies, 2026)

Hydrangea-like NiTi layered double hydroxide-derived balsawood@Ti3C2Tx-based disposable electrode for convenient residue analysis of carbendazim pesticide - Kanru Fu; Zhengri Cong; Xinghao Wang; Haocheng Sun; Yong Zhang (Chemical Engineering Journal, 2026)

10-Hydroxy-2-decenoic acid ameliorates LPS-induced acute lung injury through targeting MD2-mediated inflammatory signaling pathways - Cong Shu; Chen Li; Huamin Liu; Zengxian Zhou; Chenghao Qian; Zhuohui Xie; Fenfen Lin; Yuxiao Jiang; Ruping Chen; Yue Liu; Xin Liu; Gaozhi Chen; et al. (Toxicology and Applied Pharmacology, 2025)

SpecGuard: A food hazardous substance detection application based on deep learning and EncodeBandCompress spectral bands compression method - Yanshen Zhao; Weiming Shi; Runzhe Zhang; Huayu Fu; Cong Wang; Xiang Ji; Zhongzhi Han (Food Control, 2025)

Phase transformation toughening behaviors of t-ZrO2 nanoparticles in glass sealing of YSZ ceramic and Crofer22H stainless steel for solid oxide fuel cell - Wei Cong; Yangfan Fu; Peng He; Tiesong Lin; Guangjie Feng; Zhanpeng Zhang; Wenlong Duan; Yifeng Wang; Qian Wang (Chemical Engineering Journal, 2025)

Identification of a missing Pictet–Spenglerase in the Gloriosa superba L. colchicine biosynthesis pathway - Jingyi Sun; Huapeng Sun; Zhiqiang Xiong; Xuefei Jiang; Xiaona Fu; Hanqing Cong; Fei Qiao (Molecular Biology Reports, 2025)

Depth-dependent velocity changes in the 2018 Kilauea eruption: insights into magma behavior - Cong Zhou; Lei Fu; Xiangzhi Zeng; Meng Zhang; Pei Zhang; Kexu Shi; Lingyun Ji; Qingliang Wang (Bulletin of Volcanology, 2025)

Postharvest biocontrol ability and antagonistic mechanism of Streptomyces djakartensis MEPS155 against Ceratocystis fimbriata in sweetpotato - Yongjing Zhang; Xiaoying Cao; Changgen Li; Hao Cong; Yujie Chen; Qiao Liu; Yiming Wang; Hailan Fu; Jiluan Zhang; Jihong Jiang; Ludan Li (Postharvest Biology and Technology, 2025)

Enhanced compatibilization of waste commingled plastics for high-quality cultivation substrate fabrication through biodegradable ingredients modulation - Shi-Lei Han; Cong-Cong Zhang; Ziyang Liu; Fu-Shen Zhang; Xiao Wang (Journal of Environmental Chemical Engineering, 2025)

Dry cleaning of food-grade plastics on a gas-solid biphase fluidized bed: Efficiency, assessment and mechanism - Ziyang Liu; Cong-Cong Zhang; Fu-Shen Zhang; Shi-Lei Han; Dai-En Yang (Journal of Environmental Chemical Engineering, 2025)

Nanoconfinement-engineered ZIF-8/polyelectrolyte gel hybrid membranes for high-efficient antibiotic separation - Wei Chen; Bing-Xin Gu; Yi-Jie Zhang; Hao Zheng; Yan-Li Ji; Quan-Fu An; Cong-Jie Gao (Chemical Engineering Journal, 2025)

What Controls the Distribution of Ore Veins in Quartz Vein-Type Tungsten Deposits: Constrains from Fan-Shaped Mineralization in SE China - Gui-Cong Fang; Deng-Hong Wang; Fu-Qiang Yang; Zhan-Xu Ni; Chang-Shuai Huang; Ping Wang; Meng Feng; Zuo-Hai Feng (Journal of Earth Science, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

S-domain receptor-like protein kinase OsGRSK1 participates in regulating plant height and grain size via gibberellin pathway in rice - Cong Chen; Xin Hu; Haitao Du; Quanshi Dong; Yihan Fu; Ying Li; Fanqing Duanmu; Hongzheng Sun; Junzhou Li; Changqing Du (Plant Science, 2025)

Efficient sweet potato quality detection using pruned attention-based deep learning - Huayu Fu; Guosheng Xin; Yanshen Zhao; Cong Wang; Zhongzhi Han (Journal of Stored Products Research, 2025)

New clicked hydrophobic 2,9-bis-triazolyl-1,10-phenanthroline ligands used as extractants for actinide/lanthanide separation: Towards deep purification - Xuan Fu; Yang Liu; Heng-Yi Zhou; Cong-Zhi Wang; Tao-Yuan Xiu; Zhe Xiao; Hong-Bin Tang; Zhi-Wei Huang; Zhi-Heng Zhou; Li-Yong Yuan; Ze-Yi Yan; Wei-Qun Shi (Journal of Hazardous Materials, 2025)

BarleyOmics: A comprehensive multi-omics database of barley - Junheng Zhao; Shanggeng Xie; Chenyang Zhang; Zengjie Hu; Xiangqian Lu; Nannan Zheng; Yujie Fu; Jie Yao; Ping Zhou; Danyin Huang; Zhizhong Zhang; Mengdi Li; et al. (Molecular Plant, 2025)

Aflatoxin detection in naturally contaminated peanuts based on vision transformer and multi-scale convolutional fusion - Cong Wang; Yifan Zhao; Hongfei Zhu; Weiming Shi; Qiong Wu; Huayu Fu; Zhongzhi Han (Food Chemistry, 2025)

Achieving underpotential Mn deposition chemistry via hydrated eutectic electrolytes for aqueous manganese metal batteries - Quanhuan Yao; Linyang Li; Xue Chen; Shenghui Zhang; He Zhang; Yujie Fu; Cong Tian; Guilong Yan; Anjun Hu; Liujun Cao; Jianping Long (Chemical Engineering Journal, 2025)

Subchannel analysis of post-dryout flow and heat transfer in a tight-lattice fuel assembly - Shuo Chen; Junsen Fu; Quanyi Gao; Yubo Sun; Yao Xiao; Tenglong Cong; Hanyang Gu (Annals of Nuclear Energy, 2025)

Design and experiment of a high-speed row cleaning unit with double air spring active control system - Xiaomeng Xia; Dongyan Huang; Honggang Li; Ruiqiang Ran; Shuyan Liu; Lili Fu; Yongjian Cong (Computers and Electronics in Agriculture, 2025)

The SnRK1 kinase TaSnRK1.10 positively regulates heavy metal chromium tolerance mainly by mediating reactive oxygen species homeostasis and activating the phenylpropanoid biosynthetic pathway in wheat - Yihan Fu; Cong Chen; Pei Pei; Xiangyang Hao; Jiajia Jin; Shujie Shi; Qiang Ge; Pengfei Wang; Gezi Li; Guozhan Fu; Changqing Du; Guozhang Kang (Journal of Hazardous Materials, 2025)

Uncovering hidden dangers in urban housing: Sources of indoor radon and associated health risks - Yan Liu; Cong Fu; Yuchen Li; Wei Xu; Ziheng Huang; Yanqing Xu (Journal of Environmental Management, 2025)

Effect of epsilon-poly-L-lysine treatment on swelling, microbial growth and physicochemical quality of vacuum-packed lotus root - Qianlong Shi; Yixuan Wang; Cong Han; Xingfeng Guo; Maorun Fu; Subo Tian; Xiaofei Xin (Food Control, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Effect of temperature change patterns on thermal responses, SBS, and cognitive performance of occupants - Yuxin Wu; Angchen Jiang; Guojian Li; Xinyi Li; Cong Fu; Hong Liu; Baizhan Li (Energy and Buildings, 2025)

Paleoenvironmental changes and nitrogen cycling of the lacustrine systems following the Toarcian Oceanic Anoxic Event in the Sichuan Basin (China): Insights from nitrogen isotopes - Yang Bai; Jianfa Chen; Jin Wu; Wenzhe Gang; Václav Suchý; Cong Chen; Xuemin Xu; Rao Fu; Jiaqi Zhang; Shuaiqi Tang (Chemical Geology, 2025)

Aqueous production of sulfur-containing aerosols from nitroaromatic compounds and SO2 in wintertime urban haze - Ning Yang; Junfeng Wang; Daniel J. Jacob; Jianhuai Ye; Ming Sheng; Mutong Niu; Yiming Qin; Xinlei Ge; Yele Sun; Zifa Wang; Yuhang Wang; Fengchang Wu; et al. (Science Bulletin, 2025)

Discovery of structurally intriguing diterpenoids as anti-neuroinflammatory agents from mangrove plant Excoecaria agallocha L. via inhibiting macrophage polarization and inflammasome - Jun-Yi Li; Ming-Bin Chen; Ting-Ting Fu; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Jing Zhou; Yong Rao; Zhong-Ping Jiang; Ling Huang (Phytochemistry, 2025)

Automated physics parameter identification of tuned vibration absorber in offshore wind turbines based on unsupervised spectral clustering and SSI - Xin Chen; Naiwei Kuai; Wenwei Fu; Zhiqiang Zhang; Tong Guo; Tao Liu; Cong Liu (Ocean Engineering, 2025)

The role of clay in hydrate-based carbon emission reduction: Phenomenon, mechanisms, and application - Huiquan Liu; Shuai Wang; Yixuan Fu; Changrui Shi; Yongchen Song; Lunxiang Zhang; Cong Chen; Mingjun Yang; Zheng Ling (Fuel, 2025)

Modeling China's carbon emission reduction trajectory and peak path using a system dynamic approach - Ruoyu Dong; Cong Fu; Yan Liu; Yanqing Xu; Kenan Li (Ecological Modelling, 2025)

Effects of thinning on soil water content and water use characteristics of artificial forest in the Loess Plateau of China - Yu Liu; Yue Li; Guangyao Gao; Lei Jiao; Zongshan Li; Zhaolin Li; Cong Wang; Di Wang; Lide Tian; Bojie Fu (CATENA, 2025)

An EXPAR-CRISPR/Cas12a Assay for Rapid Detection of Salmonella - Wensen Lin; Mintao Huang; Hongjian Fu; Luxin Yu; Ying Chen; Lingwei Chen; Yanzhen Lin; Ting Wen; Xiaomin Luo; Yanguang Cong (Current Microbiology, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Impacts of cascade dam construction on riparian vegetation in an alpine region - Yihang Wang; Nan Cong; Yu Zhong; Yongshuo Fu; Nan Wang; Lijian Ouyang; Weiwei Yao (Journal of Hydrology, 2025)

Impact of particle-attached microbial denitrification on N2O production in an agricultural-urban watershed - Mengdi Yang; Hanjie Yang; Wencai Wang; Huaiyang Fang; Lu Huang; Dan Li; Lingfang Fu; Shiyuan Ding; Xiao-Dong Li; Cong-Qiang Liu; Gangjian Wei; Dongli Li; et al. (Journal of Environmental Management, 2025)

Slowing wind increases soil carbon emissions in a fragmented subtropical forest: a study combining field and model experiments - Hao-Hao Wu; Ling-Ling Zhang; Ai-Min Liao; Hua-Wu Wu; Xiao-Ming Lai; Hai-Xia Zhang; Ye Xia; Yang Cao; Zi-Chun Zhu; Zhen-Ming Ji; Cong-Sheng Fu (Plant and Soil, 2025)

Eco-friendly approach utilizing banana peel as a renewable additive for Portland cement - Jin Yang; Zhiliang Dong; Ying Su; Cong Tian; Fei Dai; Zhuoyi Fu; Gaoyuan Zhai; Bohumír Strnadel; Xingyang He (Sustainable Chemistry and Pharmacy, 2025)

Nomogram for Predicting Long-term Outcomes of Encephaloduroarteriosynangiosis in Toddlers with Moyamoya Disease: a Longitudinal and Cross-sectional Study - Qingbao Guo; Yan-Na Fan; Qian-Nan Wang; Jingjie Li; Cong Han; Zhengxing Zou; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; et al. (Translational Stroke Research, 2025)

Global Soil Methane Uptake Estimated by Scaling Up Local Measurements - Jiawei Jiang; Zhifeng Yan; Jinshi Jian; Shushi Peng; Hanqin Tian; Kendalynn A. Morris; Robert M. Ellam; Jesper Riis Christiansen; Huai Chen; Jianzhi Dong; Si‐Liang Li; Pingqing Fu; et al. (Global Change Biology, 2025)
Aerobic soils remove methane from the atmosphere, but global soil methane uptake (SMU) estimates remain highly uncertain due to challenges in scaling local data. We develop a data‐driven approach to refine this global estimate by incorporating local data of 79,800 flux measurements from 198 sites. This novel approach links the global SMU budget to local SMU fluxes by varying its parameters with soil properties. Our 2003–2018 global SMU estimate is ~39.0 Tg CH 4 year −1 —about 30% higher than existing bottom‐up estimates and consistent with top‐down assessments. Cold grasslands and deserts were found to contribute nearly 30% of the total SMU, while disturbed agricultural biomes have the lowest SMU. The projected future global SMU is shaped by temperature and atmospheric methane, though local SMU is primarily influenced by changes in soil moisture. This study emphasizes the potential of soils in climate regulation and highlights the need to focus on key biomes for a better understanding of the soil‐atmosphere methane feedback and optimizing methane management strategies.

Polysaccharide metabolic pattern of Cytophagales and Flavobacteriales: a comprehensive genomics approach - Kuo-Jian Ma; Yong-Lian Ye; Yu-Kang Li; Ge-Yi Fu; Yue-Hong Wu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2025)
The complete metabolism of carbohydrates, as the most abundant and structurally diverse organic matter on earth, requires the involvement of different carbohydrate-active enzymes (CAZymes). Flavobacteriales and Cytophagales are two groups whose members specialize in polysaccharide metabolism, but research on their polysaccharide metabolic patterns based on the overall CAZymes is scarce. In this study, we analyzed 702 filtered genomes of Flavobacteriales and Cytophagales and obtained 100,445 CAZymes. According to their taxonomic status and living environment, we explored the impact of taxonomic status, isolation source, and environmental condition on their potential polysaccharide metabolic patterns. The results indicated significant differences in the CAZyme composition among different taxonomic statuses or environments. Compared with the Flavobacteriales genomes, the genomes of Cytophagales possess more abundant and diverse CAZymes, but have fewer unique CAZyme families. Genomes from different families vary greatly in terms of CAZyme family diversity and composition, but relatively small divergences were found from families in the same order. Furthermore, our findings indicated that genomes from the marine and tidal flat environments share more similarities in CAZyme family composition and diversity compared with the terrestrial genomes. Extreme environments greatly constrain the types of CAZyme families present, and certain CAZyme families are significantly lower than those in normal environments. Although significant differences were found among genomes from both different taxonomic statuses and environments, the dimensionality reduction and the clustering analysis based on CAZyme composition indicated that evolutionary status is the main factor influencing the polysaccharide metabolic patterns of these strains. The correlations among CAZyme families indicated that the majority of these families are synergistically involved in polysaccharide metabolism. This study provides a comprehensive profile of the CAZymes in Flavobacteriales and Cytophagales, highlighting the role of evolutionary status in shaping the polysaccharide metabolic patterns and the prevalence of synergism among CAZyme families. These findings have implications for understanding microbial carbohydrate metabolism in different environments.

Hydrochemical processes and water balance trends based on stable isotopes of typical alpine lakes in the Qinghai-Tibet Plateau - Changchang Fu; Xiangquan Li; Xu Cheng; Cong Liu; Zhanxue Bai; Jinqiu Li (Journal of Geochemical Exploration, 2025)

A nationwide probabilistic risk assessment and a new insight into source-specific risk apportionment of antibiotics in eight typical river basins in China: Human health risk and ecological risk - Cong Men; Haoquan Jiang; Yuting Ma; Hengjiang Cai; Han Fu; Zifu Li (Journal of Hazardous Materials, 2025)

Analytical solutions of two-liner tunnels constructed in time-dependent plastic rocks considering loading-unloading stress paths - Hua-ning Wang; Qian Liu; Fei Song; Rui-cong Fu; Ming-jing Jiang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Rapid formation of carbon dioxide hydrate governed by the natural nano-clay for effective carbon dioxide capture - Huiquan Liu; Shuai Wang; Changrui Shi; Yongchen Song; Yixuan Fu; Zhen Li; Lunxiang Zhang; Cong Chen; Mingjun Yang; Zheng Ling (Fuel, 2025)

Constructing mullite-based catalyst by surface oxygen vacancy regulation for propane oxidation at reduced temperature - Sen Fu; Yao Nian; Changqing He; Cong Zhang; Lin He; Yong Wang; Shinee Lou; Hong Sui (Chemical Engineering Journal, 2025)

Rice Wall-Associated Protein Kinase OsWAK12 Modulates Primary Root and Root Hair Via Involving in Auxin Pathway - Changqing Du; Xin Hu; Zheng Hu; Cong Chen; Fanqing Duanmu; Yihan Fu; Lili Wang; Quanshi Dong; Hongzheng Sun; Junzhou Li; Quanzhi Zhao (Journal of Plant Growth Regulation, 2025)

A multi-verse optimizer-based CNN-BiLSTM pixel-level detection model for peanut aflatoxins - Cong Wang; Hongfei Zhu; Yifan Zhao; Weiming Shi; Huayu Fu; Yanshen Zhao; Zhongzhi Han (Food Chemistry, 2025)

Combined treatment of ɛ-polylysine and UV-C inhibited aerobic bacteria growth, and maintained the color, texture, flavor of vacuum-packed fresh-cut lettuce slices - Zhang Xin; Liu Qianqian; Han Cong; Chen Qingmin; Jiao Wenxiao; Fu Maorun (Postharvest Biology and Technology, 2024)

Biogeochemical process governing cadmium availability in sediments of typical coastal wetlands driven by drying-wetting alternation - Cheng-Cheng Jiang; Guang-Hui Yu; Xiao-Jie Zhou; Fu-Sheng Sun; Cong-Qiang Liu (Journal of Hazardous Materials, 2024)

Copper slag based catalytic material was prepared using a one-pot method to efficiently activate of peroxymonosulfate for degradation of carbamazepine - Cong Pan; Yunqiao Wang; Chenyang Fu; Jirong Lan (Journal of Environmental Chemical Engineering, 2024)

2,3-Butanedione inhibited the swelling and microbial growth, maintained flavor and quality attributes of vacuum-packed lotus root - Yixuan Wang; Qianlong Shi; Maorun Fu; Qingmin Chen; Cong Han (Food Control, 2024)

Ultrasonic-Microwave extraction of glucoside alkaloids from potato peel residue and its antibacterial activity - Zhongliang Guan; Qingmin Chen; Ye Xu; Cong Han; Min Wang; Tao Zhao; Handong Zhao; Maorun Fu (Natural Product Research, 2024)

Spatial distribution characteristics, ecological risk assessment, and source analysis of heavy metal(loid)s in surface sediments of the nearshore area of Qionghai - Junyi Jiang; Miao Fu; Jianying Yang; Yanwei Song; Guowei Fu; Hongbing Wang; Cong Lin; Yang Wang (Frontiers in Marine Science, 2024)
To understand the pollution characteristics and potential sources of heavy metal(loid)s in the nearshore sediments of Qionghai, 93 surface sediment samples were collected from the region. The concentrations of 20 elements, including Fe, Mg, Ca, Ti, Mn, Ba, Cr, Sr, Ni, Cu, Zr, As, Hg, Se, Be, Co, Mo, Cd, Ga, and Pb, were measured. The extent of contamination and ecological risk posed by these heavy metals/metalloids were evaluated using the geo-accumulation index, potential ecological risk index, and Nemerow comprehensive risk index. Additionally, correlation analysis, principal component analysis (PCA), and positive matrix factorization (PMF) were employed to identify the potential sources of these elements in the sediments. The findings reveal the following: (1) The mean concentrations of Fe, Ca, Mg, Ti, Cu, Sr, Zr, Mo, Cd, Pb, Hg, As, and Se exceed the background values for shallow sea sediments in China. Notably, Ca, Ti, Sr, Zr, Mo, Hg, and As exhibit coefficients of variation greater than 51%, indicating significant spatial variability primarily driven by anthropogenic activities. (2) The ecological risk assessment identifies Sr, Hg, and As as the principal pollutants and key potential ecological risk factors in the study area, necessitating prioritization in subsequent monitoring efforts. (3) Correlation and source analysis suggest that As and Mn primarily originate from agricultural activities, Sr, Ca, and Mg from aquaculture, Zr, Ti, Mo, Se, Pb, Be, Co, Cu, Ga, Ni, Fe, and Cd from natural sources, and Hg, Ba, and Cr from transportation sources. Additionally, this study identified Sr, Hg, and As as the primary pollutants in the Qionghai nearshore area, with sources predominantly linked to agriculture, aquaculture, and traffic. Regular monitoring will help track the effectiveness of implemented control measures and provide data for ongoing risk assessments, ensuring the protection and sustainability of the marine environment.

Genetic characteristics and pathogenicity of variant porcine parvovirus 1 in northern China - Huiwei Deng; Mengting Wang; Guangyi Cong; Fang Fu; Li Feng (Veterinary Microbiology, 2024)

A skin-inspired anisotropic multidimensional sensor based on low hysteresis organohydrogel with linear sensitivity and excellent robustness for directional perception - Shengnan Li; Zibo Xiao; Hailong Yang; Canjie Zhu; Guoqi Chen; Jingxia Zheng; Jiayuan Ren; Wenquan Wang; Yang Cong; Luqman Ali Shah; Jun Fu (Chemical Engineering Journal, 2024)

Bacterial outer membrane vesicles-clothed nanoparticles delivered by live macrophages for potentiating antitumor photoimmunotherapy - Cong Fu; Lu Tang; Yuqi Cao; Yue Yin; Hening Liu; Jingwen Feng; Jifan Gao; Jing Li; Wei Wang (Chemical Engineering Journal, 2024)

Icariin-loaded selenium-gold multi-shell nanocomposites with NIR-II response release to relieve post-damaged bone microenvironment for osteoporosis synergy therapy - Yuqing Li; Xiaotong Feng; Yuwei Li; Qile Song; Naling Long; Xiaoting Fu; Yifan Wang; Yingjiao He; Huiying Yan; Cong Li; Lina Feng; Cundong Fan; et al. (Chemical Engineering Journal, 2024)

Scalable MXene/Sepiolite film-based hydrovoltaic generators with outstanding output power - Weijing Yuan; Huiquan Liu; Yixuan Fu; Yang Zhang; Haoqi Huo; Lunxiang Zhang; Mingjun Yang; Yanghui Li; Cong Chen; Yongchen Song; Zheng Ling (Chemical Engineering Journal, 2024)

Glia dysfunction in schizophrenia: evidence of possible therapeutic effects of nervonic acid in a preclinical model - Xiaona Wang; Jiacheng Fu; Huiying Wang; Cong Liu; Yongping Zhang; Cai Song; Changhong Wang (Psychopharmacology, 2024)

Conversion and fate of waste Li-ion battery electrolyte in a two-stage thermal treatment process - Li-Jun Wu; Fu-Shen Zhang; Zhi-Yuan Zhang; Cong-Cong Zhang (Waste Management, 2024)

Multi-output prediction for TBM operation parameters based on stacking ensemble algorithm - Yu Tang; Junsheng Yang; Yuyang You; Jinyang Fu; Xiangcou Zheng; Cong Zhang (Tunnelling and Underground Space Technology, 2024)

Aridity regulates the impacts of multiple dimensional plant diversity on soil properties in the drylands of northern China - Shuhan Li; Guangyao Gao; Cong Wang; Zongshan Li; Xiaoming Feng; Bojie Fu (Science of The Total Environment, 2024)

A naturaly attenuated largemouth bass ranavirus strain provided protection for Micropterus salmoides by immersion immunization - Xiaozhe Fu; Wenxian Li; Cong Liu; Xia Luo; Qiang Lin; Yinjie Niu; Hongru Liang; Baofu Ma; Ningqiu Li (Fish & Shellfish Immunology, 2024)

Intensified O2 activation and lattice O supply at inverse oxide-metal interface for catalytic oxidation reactions: A case study in alcohol oxidation - Kun Liu; Yongbin Sun; Jiaqi Si; Cong Fu; Yushui Bi; Xiaomin Zhao; Guofeng Zhao (Chemical Engineering Journal, 2024)

Micro/nano system-mediated local treatment in conjunction with immune checkpoint inhibitor against advanced-Stage malignant melanoma - Lu Tang; Hening Liu; Yue Yin; Ting Pan; Cong Fu; Yuqi Cao; Yijun Mei; Qiaqia Xiao; Ziwei Yan; Yi Yao; Haijuan Dong; Wei Wang (Chemical Engineering Journal, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

Applications of multi-omics techniques to unravel the fermentation process and the flavor formation mechanism in fermented foods - Linfeng Wen; Lixin Yang; Cong Chen; Jun Li; Jiangyan Fu; Guo Liu; Qixin Kan; Chi-Tang Ho; Qingrong Huang; Yaqi Lan; Yong Cao (Critical Reviews in Food Science and Nutrition, 2024)

Differential enrichment mechanism of helium in the Jinqiu gas field of Sichuan Basin, China - Kaixuan Liu; Jianfa Chen; Shuaiqi Tang; Jiaqi Zhang; Rao Fu; Cong Chen; Yi Zou; Benjian Zhang; Hua Wang; Baoshou Zhang (Marine and Petroleum Geology, 2024)

Dissolved oxygen fluctuation alters dissolved organic carbon stability and can accumulate resistant fraction - Yu-Qing Li; Fu-Tao Fang; Cong Zeng; Zhuo-Yi Zhu (Marine Chemistry, 2024)

Numerical study of the effect of helical fuel rod geometry on single-phase flow and heat transfer characteristics - Junsen Fu; Junlong Li; Ziming Wang; Tenglong Cong; Hui Guo; Yao Xiao; Hanyang Gu (Annals of Nuclear Energy, 2024)

Multi-species weed detection and variable spraying system for farmland based on W-YOLOv5 - Yanlei Xu; Yukun Bai; Daping Fu; Xue Cong; Haiyang Jing; Zehao Liu; Yang Zhou (Crop Protection, 2024)

ε-Polylysine treatment maintains sensory quality, texture, flavor, and inhibits aerobic bacteria growth in vacuum-packed fresh-cut lettuce - Liu Qianqian; Zhang Xin; Han Cong; Chen Qingmin; Sun Fei; Fu Maorun; Zhao Handong; Xiao Zhijian; Tang Zheng (Postharvest Biology and Technology, 2024)

Synergistic mechanism and toxicity reduction potential in medium-pressure UV/chlorine/TiO2 system for metronidazole removal - Yu-qiong Gao; Xiang-mei Zhong; Xue-ting Ren; Fu-xiang Tian; Nai-yun Gao; Cong Li (Journal of Water Process Engineering, 2024)

Construction and examination of temperature master curve for asphalt with different aging extents - Wenhao Dong; Feng Ma; Zhen Fu; Wen Qin; Cong Qi; Jiahao He; Chen Li (Fuel, 2024)

Size-switchable and dual-targeting nanomedicine for cancer chemoimmunotherapy by potentiating deep tumor penetration and antitumor immunity - Lu Tang; Yue Yin; Ziyao Zhang; Cong Fu; Yuqi Cao; Hening Liu; Jingwen Feng; Jifan Gao; Jing Shang; Wei Wang (Chemical Engineering Journal, 2024)

Risk Factors for Preoperative Cerebral Infarction in Infants with Moyamoya Disease - Qingbao Guo; Songtao Pei; Qian-Nan Wang; Jingjie Li; Cong Han; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; Zhengxing Zou; et al. (Translational Stroke Research, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Saprobic Dothideomycetes from Yunnan, China: introducing a new species, Queenslandipenidiella lingcangensis , and a new host record for Periconia byssoides - Guang-Cong Ren; Er-Fu Yang; Jutamart Monkai; Kandawatte W. T. Chethana; Heng Gui; Antonio Roberto Gomes de Farias (New Zealand Journal of Botany, 2024)

Advancing data-driven sustainable design: A novel NEV form design approach in China's market - Zeng Wang; Shifan Niu; Cong Fu; Shijie Hu; Lingyu Huang (Journal of Cleaner Production, 2024)

Functional properties and structure of soluble dietary fiber obtained from rice bran with steam explosion treatment - Xin-Yi Tian; Jian-Fu Liu; Cong-Cong Qiao; Zhuo Cheng; Na-Na Wu; Bin Tan (Journal of Cereal Science, 2024)

Bicyclol mitigates lipopolysaccharide-induced acute lung injury through myeloid differentiation factor 88 inhibition - Lili Fu; Linting Cheng; Junliang Lu; Qianru Ye; Cong Shu; Chuchu Sun; Zhiguo Liu; Guang Liang; Weixin Zhao (Toxicology and Applied Pharmacology, 2024)

Five undescribed cyclopeptides from Cordyceps militaris - Wei Yang; Cong Fu; Bin-Yuan Hu; Yong-Ming Yan; Yong-Xian Cheng (Phytochemistry, 2024)

Overcoming research challenges: In vitro cultivation of Ameson portunus (Phylum Microsporidia) - Ming Fu; Hongnan Qu; Yongliang Wang; Jingyu Guan; Tian Xia; Kai Zheng; Liyuan Tang; Chunxue Zhou; Huaiyu Zhou; Wei Cong; Jinyong Zhang; Bing Han (Journal of Invertebrate Pathology, 2024)

Pickering extremulsion rich in lipophilic phytochemicals: Preparation, characterization and application - Xu Han; Cong-Jia Duan; Zi-Fei Wei; Jian Xu; Cheng-Dong Nie; Yuan-Hang Chang; Bo-wen Zhai; Yu-Jie Fu (Journal of Food Engineering, 2024)

An innovative and value-added approach to recycle hexafluorophosphate from waste lithium-ion batteries: New perspective of electrolyte disposal and recovery - Li-Jun Wu; Zhi-Yuan Zhang; Cong-Cong Zhang; Fu-Shen Zhang (Journal of Environmental Chemical Engineering, 2024)

Clean and efficient preparation of metallic bismuth from methane-sulfonate electrolyte in the membrane electrolysis cell - Cong Chang; Shenghai Yang; Jie Dai; Jun Li; Caiping Fu; Jingtao Cui; Weizhi Zeng; Hong Liu; Jiaqi Qi; Wei Jin; Yongming Chen (Journal of Environmental Chemical Engineering, 2024)

Bimetallic iron-copper nanozyme for determination and degradation of norfloxacin in foods - Cong Cheng; Min Han; Gang Xiang; Xiaoying Fu; Xianxing Wang; Changfang Lu (Food Chemistry, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Towards spatiotemporal-resolved spectroscopic measurement of freezing desalination using femtosecond laser filaments - Xun Cong; Shanming Chen; Yumeng He; Yao Fu; Hongwei Zang; Helong Li; Huailiang Xu (Desalination, 2024)

Investigation on evolution mechanism and treatment of invert damage in operating railway tunnels under heavy rainfall - Yubo Luo; Junsheng Yang; Yipeng Xie; Jinyang Fu; Cong Zhang (Bulletin of Engineering Geology and the Environment, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Crystal mush rejuvenation in the formation of Triassic dacites in Mengku, SE Tibetan Plateau - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; Zai-Bo Sun; Xiao-Chi Liu; De-Feng He; Wei-Qiang Ji; Fang-Yang Hu; Shao-Hua Zhang; Xiao-Ming Huang (Journal of Asian Earth Sciences, 2024)

Highly selective production of high purity methyl oleate biodiesel by silver-based deep eutectic solvent extraction - Xianli Fu; Yuxin Liu; Cong Sun; Wei Liu (Fuel, 2024)

Metagenomics and untargeted metabolomics analyses to unravel the formation mechanism of characteristic metabolites in Cantonese soy sauce during different fermentation stages - Linfeng Wen; Jianping Lei; Lixin Yang; Qixin Kan; Peipei Wang; Jun Li; Cong Chen; Liping He; Jiangyan Fu; Chi-Tang Ho; Qingrong Huang; Yong Cao. (Food Research International, 2024)

Synergistic binding mechanisms of co-contaminants in soil profiles: Influence of iron-bearing minerals and microbial communities - Fu-Sheng Sun; Miao-Miao Wang; Xiang-Yang Zhao; Qiao-Yun Huang; Cong-Qiang Liu; Guang-Hui Yu (Environmental Pollution, 2024)

Screening of Plant Essential Oils as Potato Sprout Suppressants at Low Storage Temperature - Qingmin Chen; Lixue Yuan; Zhongliang Guan; Fengli Yue; Cong Han; Maorun Fu (Potato Research, 2024)

The association between DNA methylation and human height and a prospective model of DNA methylation-based height prediction - Zhonghua Wang; Guangping Fu; Guanju Ma; Chunyan Wang; Qian Wang; Chaolong Lu; Lihong Fu; Xiaojing Zhang; Bin Cong; Shujin Li (Human Genetics, 2024)

Simultaneous generation of free radicals, Fe(IV) and Fe(V) by ferrate activation: A review - Feilong Dong; Chuyun Fu; Mingbao Feng; Da Wang; Shuang Song; Cong Li; Eric Lichtfouse; Jinzhe Li; Qiufeng Lin; Virender K. Sharma (Chemical Engineering Journal, 2024)

FinTech and sustainable financing for low carbon energy transitions: A biodiversity and natural resource perspective in BRICS economies - Li Zeng; Wing-Keung Wong; Hu Fu; Haitham A. Mahmoud; Phan The Cong; Dinh Thi Thanh Thuy; Pham Xuan Bach (Resources Policy, 2024)

Study on the dynamic effects of plateau hypoxic and cold environment on the thermal adaptation of short-term sojourners in Xizang - Guannan Duan; Cong Song; Yanfeng Liu; Zhiguo Fu; Cong Zhang; Xu Han; Yong Li; Yong Zhou (Journal of Thermal Biology, 2024)

Exploring spatial-temporal driving factors for changes in multiple ecosystem services and their relationships in West Liao River Basin, China - Wei Jiang; Bojie Fu; Guangyao Gao; Yihe Lv; Cong Wang; Siqi Sun; Kai Wang; Stefan Schüler; Zhongguo Shu (Science of The Total Environment, 2023)

Survey on the dressing behavior and thermal comfort of plateau Tibetan people - Dongxue Zhao; Yanfeng Liu; Cong Song; Zhiguo Fu; Cong Zhang; Jinyu Zhao; Jia Li (Building and Environment, 2023)

Mitochondrial dysfunction: a new molecular mechanism of intervertebral disc degeneration - Chao Song; Yulin Xu; Qinghua Peng; Rui Chen; Daqian Zhou; Kang Cheng; Weiye Cai; Tao Liu; Chenyi Huang; Zhijiang Fu; Cong Wei; Zongchao Liu (Inflammation Research, 2023)

Chidamide inhibits cell glycolysis in acute myeloid leukemia by decreasing N6-methyladenosine-related GNAS-AS1 - Changmei Hu; Xiao Fu; Shujun Li; Cong Chen; Xielan Zhao; Jie Peng (DARU Journal of Pharmaceutical Sciences, 2023)

Systemic subchronic toxicity and comparison of four selenium nutritional supplements by 90-day oral exposure in Sprague-Dawley rats - Lu Yu; Yanmei Li; Wen Qu; Yanhua Zheng; Xuejiao Chen; Shaohua Fu; Jingjing Qu; Jie Tian; Shuiyuan Cheng; Xin Cong; Bolin Fan; Chunhong Wang (Food and Chemical Toxicology, 2023)

Effect of Particle Size Distributions (PSDs) on ground responses induced by tunnelling in dense coarse-grained soils: A DEM investigation - Yipeng Xie; Junsheng Yang; Xiangcou Zheng; Tongming Qu; Cong Zhang; Jinyang Fu (Computers and Geotechnics, 2023)

Spatial and molecular variations in forest topsoil dissolved organic matter as revealed by FT-ICR mass spectrometry - Ming Sheng; Shuang Chen; Cong-Qiang Liu; Qinglong Fu; Donghuan Zhang; Wei Hu; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (Science of The Total Environment, 2023)

L-type lectin receptor-like kinase OsCORK1 as an important negative regulator confers copper stress tolerance in rice - Ke Wang; Shen Li; Zhaoyan Yang; Cong Chen; Yihan Fu; Haitao Du; Hongzheng Sun; Junzhou Li; Quanzhi Zhao; Changqing Du (Journal of Hazardous Materials, 2023)

Contamination characteristics and potential health risk of brominated flame retardants in paddy soils and rice plants around a typical e-waste recycling site in south China - Kailun Luo; Zhihua Qiao; Weiyu Liang; Cong Lu; Mengru Fu; Shanqi Zhou; Yanna Han; Cheng Peng; Wei Zhang (Environmental Pollution, 2023)

Impact of wild fish faeces to deep sea dissolved organic carbon as revealed by laboratory incubations - Zhuo-Yi Zhu; Fu-Tao Fang; Shipan Hossen; Yuan Zhao; Zuo-Zhi Chen; Cong Zeng; Meng Zhou (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

4D printing of biomimetic anisotropic self-sensing hydrogel actuators - Shengnan Li; Hailong Yang; Guoqi Chen; Jingxia Zheng; Wenquan Wang; Jiayuan Ren; Canjie Zhu; Yabin Yang; Yang Cong; Jun Fu (Chemical Engineering Journal, 2023)

The heterogeneity of microbial diversity and its drivers in two types of sediments from tidal flats in Beibu Gulf, China - Yong-Lian Ye; Kuo-Jian Ma; Yun-Han Fu; Zhi-Cheng Wu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Mudflats and sandflats are two common types of coastal tidal flats, the structure and function differences of microbial communities between them are still underappreciated. Beibu Gulf is a diurnal tidal regime located in China, the differences between the two type of tidal flats could be more distinct. In this study, we collected a total of 6 samples from Beibu Gulf, consisting of 3 sandflats samples and 3 mudflats samples, classified based on clay and silt content. Generally, the mudflats samples exhibited higher levels of NH 4 + _N and TOC, but lower in ORP and pH. The microbial diversity of the two types of tidal flats was investigated, revealing great differences existed and sandflats had higher microbial richness and diversity than mudflats. Furthermore, we analyzed the association between microbial communities and environmental factors, finding NH 4 + _N to have the highest contribution to the total variation in microbial community structure, and microbial groups such as Desulfobacterota, Campilobacterota, Chloroflexota, Calditrichota, Spirochaetota, Zixibacteria, Latescibacterota and Sva0485 group in mudflats were positively associated with NH 4 + _N. The functions of microbial community were predicted using metagenomic sequences and metagenome assembled genome (MAG). Mudflats contained more genes for carbon fixation. Nitrate and nitrite reduction were widely existed in mudflats and sandflats, but nitrogen fixation was only existed in mudflats, and Campilobacterota , Desulfobacterota and Gammaproteobacteria MAGs were mainly responsible for it. Sandflats composed more genes for ammonium oxidation, but no MAG was found whether in sandflats or mudflats. Microbes in mudflats exhibited a greater abundance of genes related to sulfur cycling, especially in reduction process, unique MAGs in mudflats such as Calditrichota, Chloroflexota, Desulfobacterota and Zixibacteria MAGs are responsible for sulfate and sulfite reduction. Finally, we predicted functions of ammonium related microbes in mudflats based on MAGs and found Campilobacterota and Desulfobacterota MAGs were important for high accumulation of ammonium in mudflats. This study illuminated the structural and functional differences of microbial communities in mudflats and sandflats, providing new insights into the relationship of microbial communities and environment in the tidal flat.

Contribution of dissolved organic matter to seawater salinity measured by optic refractometer: a case study of DOM extracted from Aoshan Bay - Cong Zhang; Yuyang Xiao; Wenyue Gao; Yujie Fu; Zhensong Zhou; Shiyu Chen; Juan Su; Chi Wu; Albert Wu (Frontiers in Marine Science, 2023)
Dissolved organic matter (DOM) in seawater, consisted of a complex mixture of compounds and accounted for about 90% of marine organic carbon, is an important part of the global carbon cycle and also a part of absolute salinity of seawater. As the components of DOM are non-ionized in seawater, electric conductivity measurement cannot observe its contribution to salinity, which could lead to measurement error in salinity. Salinity measurement based on optic refractive index could reveal contribution of all dissolved matters in seawater including both non-ionized and ionized components. In this paper, a comparative study of DOM contribution to the salinity measurement by optic refractive index method and electric conductivity method was carried out for the first time. Adding DOM, extracted from Aoshan Bay, Qingdao, China, into Chinese Standard Seawater, our experimental results showed an increase of optic refractive index at 1.19×10 -4 ± 4×10 -6 per 1g/kg of DOM, which corresponds to a practical salinity increase of 0.697 ± 0.036 PSU per 1 g/kg of DOM. While, the conductivity of seawater measured by a conductivity-temperature sensor showed a decrease of 0.00065 ± 0.00008 mS/cm per 1 g/kg of DOM, which corresponded to a decrease of salinity at 0.00052 ± 0.00007 PSU per 1 g/kg of DOM. By comparing the optic and electric measurement results, the contribution of non-conductive components in the dissolved organic matters to salinity could be distinguished, which has great significance for the measurement of absolute salinity, global carbon cycle etc.

Identification and contribution of potential sources to atmospheric lead pollution in a typical megacity: Insights from isotope analysis and the Bayesian mixing model - Wen-Jing Dai; Xiao-Dong Li; Yu-Cong Fu; Shi-Yuan Ding; Qin-Kai Li; Zhi-Qi Zhao (Science of The Total Environment, 2023)

Neuroprotective effect of salidroside on hippocampal neurons in diabetic mice via PI3K/Akt/GSK-3β signaling pathway - Xue-Hua Wang; Zhong-Fu Zuo; Lu Meng; Qi Yang; Pan Lv; Li-Pan Zhao; Xiao-Bai Wang; Yu-Fei Wang; Ying Huang; Cong Fu; Wen-Qiang Liu; Xue-Zheng Liu; et al. (Psychopharmacology, 2023)

Organic carbon preservation in wetlands: Iron oxide protection vs. thermodynamic limitation - Fu-Sheng Sun; Chao Ma; Guang-Hui Yu; Yakov Kuzyakov; Yun-Chao Lang; Ping-Qing Fu; Li-Jun Guo; Hui Henry Teng; Cong-Qiang Liu (Water Research, 2023)

Transcription factor ELK1 regulates the expression of histone 3 lysine 9 to affect developmental potential of porcine preimplantation embryos - Yuanshen Zhao; Yanhui Zhai; Cong Fu; Lijing Shi; Xiangjie Kong; Qi Li; Hao Yu; Xinglan An; Sheng Zhang; Ziyi Li (Theriogenology, 2023)

Organic aerosols in the inland Tibetan Plateau: New insights from molecular tracers - Xin Wan; Pingqing Fu; Shichang Kang; Kimitaka Kawamura; Guangming Wu; Quanlian Li; Shaopeng Gao; Zhiyuan Cong (Science of The Total Environment, 2023)

Identification and functional study of detoxification-related genes in response to tolfenpyrad stress in Glyphodes pyloalis Walker (Lepidoptera: Pyralidae) - Xin Pan; Jian-Hao Ding; Shuai-Qi Zhao; Hui-Cong Shi; Wang-Long Miao; Fu-An Wu; Sheng Sheng; Wei-Hong Zhou (Pesticide Biochemistry and Physiology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Genomic and phylotypic properties of three novel marine Bacteroidota from bare tidal flats reveal insights into their potential of polysaccharide metabolism - Kuo-Jian Ma; Yong-Lian Ye; Yun-Han Fu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Special geographical location and abundant organic matter profiles in tidal flats have resulted in great microbial diversity, in which Bacteroidota strains are considered as one of the primary degraders of polysaccharides, playing a crucial role in the carbon cycle. In this study, we collected sediment or sand samples from 34 bare tidal flats in China and investigated the profile of culturable bacteria, selected three Bacteroidota for polyphasic taxonomic analysis and revealed their polysaccharide metabolic potential. Totally, we isolated 352 pure cultured bacteria and they mainly distributed in Bacteroidota , Pseudomonadota , Bacillota , and Actinomycetota . It is shown that the bare tidal flats contained a large number of potential novel species, mainly distributed in Flavobacteriales and Cytophagales within Bacteroidota . Three Bacteroidota strains, M17 T , M82 T , and M415 T , isolated from mudflat were selected for polyphasic taxonomic analysis. The 16S rRNA gene sequence similarity between strain M17 T and Mangrovivirga cuniculi KCTC 72349 T was 99.28%, and less than 90.09% with other species; strain M82 T shared the highest 16S rRNA gene sequence similarity of 97.85% with Pontibacter litorisediminis KCTC 52252 T , and less than 97.43% with other species; strain M415T had higher 16S rRNA gene sequence similarities with type species of genera Eudoraea (92.62-93.68%), Zeaxanthinibacter (92.02-92.91%), and Muriicola (92.21-92.83%). Phylogenetic analysis based on 16S rRNA gene sequences and single-copy orthologous clusters showed that strains M17 T and M82 T represent novel species within the genus Mangrovivirga and Pontibacter , respectively, and strain M415 T represents a novel species of a novel genus within the family Flavobacteriaceae . The potential in polysaccharide metabolism of all these three strains was analyzed by genomes. The analysis revealed that glycoside hydrolases and glycosyltransferases account for more than 70% of the total CAZymes. Additionally, the numbers of polysaccharide utilization loci (PULs) and annotated CAZymes in Cytophagales spp. M17 T and M82 T were found to be higher than those in Flavobacteriales sp. M415 T . Highly specialized saccharolytic systems and the presence of numerous diversified CAZymes for obtaining energy through polysaccharide metabolism were speculated to help the three novel strains adapt to the utilization of both terrestrial and marine polysaccharides.

Biochar supported nanoscale zero-valent iron for the kinetics removal and mechanism of decabromodiphenyl ethane in the sediment - Cong Lu; Xuan Zhao; Zhihua Qiao; Kailun Luo; Shanqi Zhou; Mengru Fu; Cheng Peng; Wei Zhang (Environmental Science and Pollution Research, 2023)

Utilization of constructed wetland technology in China's sponge city scheme under carbon neutral vision - Yamei Cai; Yaqian Zhao; Ting Wei; Wei Fu; Cheng Tang; Yujie Yuan; Qi Yin; Cong Wang (Journal of Water Process Engineering, 2023)

Upregulation of mitochondrial calcium uniporter contributes to paraquat-induced neuropathology linked to Parkinson’s disease via imbalanced OPA1 processing - Weixia Duan; Cong Liu; Jie Zhou; Qin Yu; Yu Duan; Tian Zhang; Yuanyuan Li; Guanyan Fu; Yapei Sun; Jiacheng Tian; Zhiqin Xia; Yingli Yang; et al. (Journal of Hazardous Materials, 2023)

Effect of boron and nitrogen modulation in metal atoms anchoring on flower-like carbon superstructure for efficient ammonia electrosynthesis - Yanchao Zhao; Shuo Zhang; Cong Han; Qian Lu; Qiuju Fu; Huimin Jiang; Lingzhi Yang; Yanlong Xing; Qiuju Zheng; Jianxing Shen; Liting Yan; Xuebo Zhao (Chemical Engineering Journal, 2023)

Light-driven uranyl-organic frameworks used as signal-enhanced photoelectrochemical sensors for monitoring anthrax - Guang Che; Weiting Yang; Cong Wang; Meiling Li; Xinyi Li; Yamin Fu; Qinhe Pan (Analytica Chimica Acta, 2023)

Inhibitory effect of ε-poly-L-lysine on fruit Colletotrichum gloeosporioides through regulating organic acid metabolism and exerting membrane-targeted antifungal activity - Jingjing Wu; Jingjing Hu; Wenxiao Jiao; Yamin Du; Cong Han; Qingmin Chen; Xin Chen; Maorun Fu (Postharvest Biology and Technology, 2023)

Fe(VI) activation system mediated by a solar-driven TiO2 nanotubes electrode for CLQ degradation: Performances, mechanisms and pathways - Jinzhe Li; Chuyun Fu; Qiufeng Lin; Tao Zeng; Da Wang; Xinwen Huang; Shuang Song; Cong Li; Feilong Dong (Journal of Hazardous Materials, 2023)

Experimental and simulation study on hydroxyl group promoting low-temperature oxidation of active groups in coal - Xun Zhang; Bing Lu; Jing Zhang; Xiang Fu; Hanzhong Deng; Ling Qiao; Cong Ding; Fei Gao (Fuel, 2023)

Soil nitrogen transformation in different land use and implications for karst soil nitrogen loss controlling - Zhong-Jun Wang; Fu-Jun Yue; Li-Li Xue; Yu-Chun Wang; Cai-Qing Qin; Jie Zeng; Hu Ding; Yu-Cong Fu; Si-Liang Li (CATENA, 2023)

The occurrence, formation and transformation of disinfection byproducts in the water distribution system: A review - Feilong Dong; Jiani Zhu; Jinzhe Li; Chuyun Fu; Guilin He; Qiufeng Lin; Cong Li; Shuang Song (Science of The Total Environment, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

An environmentally friendly process for selective recovery of lithium and simultaneous synthesis of LiFe5O8 from spent LiFePO4 battery by mechanochemical - Lixiang Wu; Fu-Shen Zhang; Zhi-Yuan Zhang; Cong-Cong Zhang (Journal of Cleaner Production, 2023)

Constitutive model for Ya’an mudstone based on mesoscopic breakage mechanism - Yun-yong He; Cong Chen; Fu-ming Wang; Cheng-chao Guo; Bo Xiang; Di Yu; En-long Liu; Chun Ding (Journal of Mountain Science, 2023)

Source availability and hydrological connectivity determined nitrate-discharge relationships during rainfall events in karst catchment as revealed by high-frequency nitrate sensing - Fu-Jun Yue; Si-Liang Li; Susan Waldron; David M. Oliver; Xi Chen; Pan Li; Tao Peng; Cong-Qiang Liu (Water Research, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Size-Resolved Characteristics and Sources of Inorganic Ions, Carbonaceous Components and Dicarboxylic Acids, Benzoic Acid, Oxocarboxylic Acids and α-Dicarbonyls in Wintertime Aerosols from Tianjin, North China - Subba Rao Devineni; Chandra Mouli Pavuluri; Shuang Wang; Lujie Ren; Zhanjie Xu; Peisen Li; Pingqing Fu; Cong-Qiang Liu (Aerosol Science and Engineering, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Environmental fate of five brominated flame retardants co-exposure in a water-sediment-zebrafish microcosm system: Enrichment, removal, and metabolism mechanisms - Zhihua Qiao; Yawen Wang; Cong Lu; Siyuan Ling; Shanqi Zhou; Mengru Fu; Kailun Luo; Cheng Peng; Wei Zhang; Bingsheng Zhou (Journal of Cleaner Production, 2023)

Socioeconomic development alters the effects of ‘green’ and ‘grain’ on evapotranspiration in China's loess plateau after the grain for green programme - Cong Wang; Bojie Fu; Yihe Lü; Yunfei Liu (Journal of Environmental Management, 2023)

A novel ternary deep eutectic solvent pretreatment for the efficient separation and conversion of high-quality gutta-percha, value-added lignin and monosaccharide from Eucommia ulmoides seed shells - Cong-Jia Duan; Xu Han; Yuan-Hang Chang; Jian Xu; Gan-Lu Yue; Ying Zhang; Yu-Jie Fu (Bioresource Technology, 2023)

Porewater dissolved inorganic carbon released due to artificial sediment scouring in the Yellow River - Xing-yu Huang; Dong Zhang; Fu-shun Wang; Zhi-qi Zhao; Ai-chun Chen; Jun-wen Zhang; Cong Zhang; Li Wu; Yu-hong Li; Bing-juan Ma; Qi-yan Feng (Applied Geochemistry, 2023)

Microbial functional communities and the antibiotic resistome profile in a high-selenium ecosystem - Yanmei Sun; Jia Guo; Fu Wei; Xiaohui Chen; Meng Li; Chao Li; Size Xia; Guangming Zhang; Wencai You; Xin Cong; Tian Yu; Shiwei Wang (Chemosphere, 2023)

A carbothermic hybrid synthesized using waste halogenated plastic in sub/supercritical CO2 and its application for lithium recovery - Cong-Cong Zhang; Fu-Shen Zhang; Neng-min Zhu; Xiao-Hui Yue (Environmental Research, 2023)

A quantitative evaluation method for granular skeleton state of binary soils at arbitrary relative density - Yipeng Xie; Junsheng Yang; Cong Zhang; Tongming Qu; Shuying Wang; Jinyang Fu (Computers and Geotechnics, 2023)

Machine Learning-Enabled Determination of Diffuseness of Brain Arteriovenous Malformations from Magnetic Resonance Angiography - Yuming Jiao; Jun-Ze Zhang; Qi Zhao; Jia-Qi Liu; Zhen-Zhou Wu; Yan Li; Hao Li; Wei-Lun Fu; Jian-Cong Weng; Ran Huo; Shao-Zhi Zhao; Shuo Wang; et al. (Translational Stroke Research, 2022)

Derivation of new resistance principle on flow-induced morphological response of flexible vegetation - Feng-Cong Jia; Wei-Jie Wang; Ling-Hua Liu; Jin-Jin Li; Ai-Ping Huang; Jing Zhang; Yi-Cheng Fu; Yang Yu (Environmental Science and Pollution Research, 2022)

Synthesis of Lanthanum-Modified Attapulgite and Its Phosphorus-Fixing Mechanism for Urban Eutrophic Lake - Lingfeng Ye; Ye Li; Cong Liu; Bolin Li; Dongxue Liu; Chang Liu; Jie Wan; Chengbin Fu (Water, Air, & Soil Pollution, 2022)

Cytokine storm and targeted therapy in hemophagocytic lymphohistiocytosis - Han-qi Zhang; Si-Wei Yang; Yi-Cheng Fu; Ming-Cong Chen; Cheng-Hao Yang; Ming-Hua Yang; Xiao-Dan Liu; Qing-Nan He; Hua Jiang; Ming-Yi Zhao (Immunologic Research, 2022)

Analysis of efficient operation conditions of the Shuang 6 gas storage in Shuangtaizi Oilfield, LiaoHe Basin, China - Jianda Li; Lingdong Meng; Xiaofei Fu; Yejun Jin; Mingming Jiang; Cong Liu (Arabian Journal of Geosciences, 2022)

PPARγ Dysfunction in the Medial Prefrontal Cortex Mediates High-Fat Diet-Induced Depression - Cong-Cong Fu; Xin-Yi Zhang; Liu Xu; Hui-Xian Huang; Shuang Xu; Qiao-Qi Wu; Zhen Wang; Xi Gu; Li-Fang Lin; Song Lin; Ying-Ying Fang; Xiong Cao; et al. (Molecular Neurobiology, 2022)

Oral Enrichment of Streptococcus and its Role in Systemic Inflammation Related to Monocyte Activation in Humans with Cocaine Use Disorder - Xiaoyu Fu; Da Cheng; Zhenwu Luo; Amanda Wagner; Sylvia Fitting; Xiaomei Cong; Wanli Xu; Kendra Maas; Zhuang Wan; Jian Zhu; Zejun Zhou; William W. Stoops; et al. (Journal of Neuroimmune Pharmacology, 2022)

Community Competition Is the Microorganism Feedback to Sedimentary Carbon Degradation Process in Aquaculture Tidal Flats - Min Zhou; Fu-Tao Fang; Cong Zeng; Li-Hong Zhang; Cheng-Xu Zhou; Zhuo-Yi Zhu (Frontiers in Marine Science, 2022)
How the microbial community response to carbon degradation is unclear, while it plays an essential role in predicting microbial community shift and determining carbon cycling. Surface sediments in two contrasting aquacultural tidal flat sites in Fujian Province, China, were collected in October, 2020. In addition to 16s rRNA gene high-throughput sequencing for determining bacteria and archaea biodiversity, an amino acids-based molecular degradation index DI was used to quantify the carbon degradation status. The results revealed that the microorganism response to DI at the family level was community competition. Specifically, the winning microbes that grew under carbon degradation (i.e., operational taxa unit numbers negatively related with the degradation index) accounted for only 18% of the total family number, but accounted for 54% of the total operational taxa unit numbers. Network analysis confirmed the oppressive relation between winners and the rest (losers + centrists), and further suggested the losers survival strategy as uniting the centrists. These findings shed new light on microorganism feedback to carbon degradation, and provide a scientific basis for the explanation of microbial community shift under progressive carbon degradation.

Response to concerns about the African fire trends controlled by precipitation over recent decades - Fangli Wei; Shuai Wang; Bojie Fu; Martin Brandt; Naiqing Pan; Cong Wang; Rasmus Fensholt (Global Change Biology, 2022)

Petrogenesis of the Late Triassic Mengsong strongly peraluminous granites in the southeastern Tibetan Plateau: highly fractionated from crystal mush - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; De-Feng He; Zai-Bo Sun; Xiao-Ming Huang; Zhi-Zhong Hu; Han Zhao (International Geology Review, 2022)

Classification of ASD based on fMRI data with deep learning - Lizhen Shao; Cong Fu; Yang You; Dongmei Fu (Cognitive Neurodynamics, 2021)

Deciphering the rhizobacterial assemblages under the influence of genetically engineered maize carrying mcry genes - Aliya Fazal; Zhongling Wen; Minkai Yang; Yonghui Liao; Jiangyan Fu; Cong He; Xuan Wang; Wencai Jie; Farman Ali; Dongqing Hu; Tongming Yin; Zhi Hong; et al. (Environmental Science and Pollution Research, 2021)

Lipidomic analyses reveal enhanced lipolysis in planthoppers feeding on resistant host plants - Xiaohong Zheng; Yeyun Xin; Yaxin Peng; Junhan Shan; Ning Zhang; Di Wu; Jianping Guo; Jin Huang; Wei Guan; Shaojie Shi; Cong Zhou; Rongzhi Chen; et al. (Science China Life Sciences, 2021)

Pinocembrin-7-Methylether Protects SH-SY5Y Cells Against 6-Hydroxydopamine-Induced Neurotoxicity via Modulating Nrf2 Induction Through AKT and ERK Pathways - Zhi-Cong Zou; Ji-Jun Fu; Yuan-Ye Dang; Qian Zhang; Xiu-Fen Wang; Han-Bin Chen; Xue-Jing Jia; Simon Ming-Yuen Lee; Chu-Wen Li (Neurotoxicity Research, 2021)

An overview of chitosan and its application in infectious diseases - Qingye Meng; Ying Sun; Hailin Cong; Hao Hu; Fu-Jian Xu (Drug Delivery and Translational Research, 2021)

Aestuariibaculum sediminum sp. nov., a marine bacterium isolated from a tidal flat in Zhoushan - Zhi-Cheng Wu; Xin-Yin Zhang; Cong Sun; Lin Xu; Ge-Yi Fu; Xue-Wei Xu (Archives of Microbiology, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

The role of MYB proto-oncogene like 2 in tamoxifen resistance in breast cancer - Xia Li; Xi Zhang; Cong-Cong Wu; Ping-Ping Li; Yi-Mou Fu; Li-Hua Xie; Shuang-Shuang Sun; Ying-Ying Zhou; Bao-Ling Zhu (Journal of Molecular Histology, 2021)

Nonlinear dynamics of fires in Africa over recent decades controlled by precipitation - Fangli Wei; Shuai Wang; Bojie Fu; Martin Brandt; Naiqing Pan; Cong Wang; Rasmus Fensholt (Global Change Biology, 2020)
Dynamics of fires in Africa are of critical importance for understanding changes in ecosystem properties and effects on the global carbon cycle. Given increasing fire risk from projected warming on the one hand and a documented human‐driven decline in fires on the other, it is still unknown how the complex interplay between climate and human factors affects recent changes of fires in Africa. Moreover, the impact of recent strong El Niño events on fire dynamics is not yet known. By applying an ensemble empirical mode decomposition method to satellite‐derived fire burned area, we investigated the spatio‐temporal evolution of fires in Africa over 2001–2016 and identified the potential dominant drivers. Our results show an overall decline of fire rates, which is continuous over the time period and mainly caused by cropland expansion in northern sub‐Saharan Africa. However, we also find that years of high precipitation have caused an initial increase in fire rates in southern Africa, which reversed to a decline in later years. This decline is caused by a high frequency of dry years leading to very low fuel loads, suggesting that recent drought causes a general reduction of burned areas, in particular in xeric savannas. In some mesic regions (10°–15°S), solar radiation and increased temperature caused increase in fires. These findings show that climate change overrules the impact of human expansion on fire rates at the continental scale in Africa, reducing the fire risk.

Deformation characteristics and failure mechanism of a reactivated landslide in Leidashi, Sichuan, China, on August 6, 2019: an emergency investigation report - Weile Li; Bo Zhao; Qiang Xu; Fan Yang; Hao Fu; Cong Dai; Xinxin Wu (Landslides, 2020)

Response of Soil Moisture to Rainfall Event in Black Locust Plantations at Different Stages of Restoration in Hilly-gully Area of the Loess Plateau, China - Weiliang Chen; Zongshan Li; Lei Jiao; Cong Wang; Guangyao Gao; Bojie Fu (Chinese Geographical Science, 2020)

The Complete Genome of Emcibacter congregatus ZYLT, a Marine Bacterium Encoding a CRISPR-Cas 9 Immune System - Zhe Zhao; Rui-an Zhang; Ge-yi Fu; Ran Zhang; Yan-fang Nie; Cong Sun; Min Wu (Current Microbiology, 2020)

Shaking table test of seismic responses of anchor cable and lattice beam reinforced slope - Jian-jing Zhang; Jia-yong Niu; Xiao Fu; Li-cong Cao; Qiang Xie (Journal of Mountain Science, 2020)

CRISPR/Cas9 facilitates genomic editing for large-scale functional studies in pluripotent stem cell cultures - Xiao-Fei Li; Yong-Wei Zhou; Peng-Fei Cai; Wei-Cong Fu; Jin-Hua Wang; Jin-Yang Chen; Qi-Ning Yang (Human Genetics, 2019)

Soil moisture–plant interactions: an ecohydrological review - Cong Wang; Bojie Fu; Lu Zhang; Zhihong Xu (Journal of Soils and Sediments, 2019)

Overexpression of two cold-responsive ATAF-like NAC transcription factors from fine-stem stylo (Stylosanthes guianensis var. intermedia) enhances cold tolerance in tobacco plants - Peng-Lin Zhan; Shan-Wen Ke; Pan-Yu Zhang; Cong-Cong Zhou; Bei-Ling Fu; Xiang-Qian Zhang; Tian-Xiu Zhong; Shu Chen; Xin-Ming Xie (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Small-world indices via network efficiency for brain networks from diffusion MRI - Lan Lin; Zhenrong Fu; Cong Jin; Miao Tian; Shuicai Wu (Experimental Brain Research, 2018)

Analysis of a broad range of perfluoroalkyl acids in accipiter feathers: method optimization and their occurrence in Nam Co Basin, Tibetan Plateau - Yili Li; Ke Gao; Bu Duo; Guoshuai Zhang; Zhiyuan Cong; Yan Gao; Jianjie Fu; Aiqian Zhang; Guibin Jiang (Environmental Geochemistry and Health, 2018)

Spatial Properties of Mismatch Negativity in Patients with Disorders of Consciousness - Xiaoyu Wang; Rao Fu; Xiaoyu Xia; Xueling Chen; Han Wu; Nicole Landi; Ken Pugh; Jianghong He; Fengyu Cong (Neuroscience Bulletin, 2018)

Seismic responses of the steel-strip reinforced soil retaining wall with full-height rigid facing from shaking table test - Li-cong Cao; Xiao Fu; Zhi-jia Wang; Yong-yi Zhou; Fei-cheng Liu; Jian-jing Zhang (Journal of Mountain Science, 2018)

High copper recovery from scrap printed circuit boards using poly(ethylene glycol)/sodium hydroxide treatment - Cong-Cong Zhang; Fu-Shen Zhang (Environmental Chemistry Letters, 2018)

Cropland physical disturbance intensity: plot-scale measurement and its application for soil erosion reduction in mountainous areas - Ming Li; Yu-kuan Wang; Pei Xu; Bin Fu; Cong-shan Tian; Shan Wang (Journal of Mountain Science, 2018)

Anti-complementary constituents of Viola kunawarensis - Hui Wang; Wen-Li Cong; Ze-long Fu; Dao-Feng Chen; Qi Wang (Natural Product Research, 2017)

The Study of Graph Measurements for Hub Identification in Multiple Parcellated Brain Networks of Healthy Older Adult - Cong Jin; Yi-Ping Chao; Lan Lin; Zhenrong Fu; Baiwen Zhang; Shuicai Wu (Journal of Medical and Biological Engineering, 2017)

Exploring the Potential of Naturalized Plants for Phytoremediation of Heavy Metal Contamination - Wei Fu; Kai Huang; Hong-Hong Cai; Jian Li; De-Li Zhai; Zhi-Cong Dai; Dao-Lin Du (International Journal of Environmental Research, 2017)

Value recovery from end-of-use products facilitated by automated dismantling planning - Liang Cong; Fu Zhao; John W. Sutherland (Clean Technologies and Environmental Policy, 2017)

KIFC1 and myosin Va: two motors for acrosomal biogenesis and nuclear shaping during spermiogenesis of Portunus trituberculatus - Dan-Dan Ma; Meng-Ying Pan; Cong-Cong Hou; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2017)

Measurement and modeling of nitrous and nitric oxide emissions from a tea field in subtropical central China - Dan Chen; Yong Li; Cong Wang; Xiaoqing Fu; Xinliang Liu; Jianlin Shen; Yi Wang; Runlin Xiao; De Li Liu; Jinshui Wu (Nutrient Cycling in Agroecosystems, 2017)

Seroprevalence and risk factors of bovine viral diarrhoea virus (BVDV) infection in yaks (Bos grunniens) in northwest China - Jian-Gang Ma; Wei Cong; Fu-Heng Zhang; Sheng-Yong Feng; Dong-Hui Zhou; Yi-Ming Wang; Xing-Quan Zhu; Hong Yin; Gui-Xue Hu (Tropical Animal Health and Production, 2016)

Strong impacts of daily minimum temperature on the green‐up date and summer greenness of the Tibetan Plateau - Miaogen Shen; Shilong Piao; Xiaoqiu Chen; Shuai An; Yongshuo H. Fu; Shiping Wang; Nan Cong; Ivan A. Janssens (Global Change Biology, 2016)
Understanding vegetation responses to climate change on the Tibetan Plateau ( TP ) helps in elucidating the land–atmosphere energy exchange, which affects air mass movement over and around the TP . Although the TP is one of the world's most sensitive regions in terms of climatic warming, little is known about how the vegetation responds. Here, we focus on how spring phenology and summertime greenness respond to the asymmetric warming, that is, stronger warming during nighttime than during daytime. Using both in situ and satellite observations, we found that vegetation green‐up date showed a stronger negative partial correlation with daily minimum temperature ( T min ) than with maximum temperature ( T max ) before the growing season (‘preseason’ henceforth). Summer vegetation greenness was strongly positively correlated with summer T min , but negatively with T max . A 1‐K increase in preseason T min advanced green‐up date by 4 days ( P P 0.01). In contrast, increases in preseason T max did not advance green‐up date ( P > 0.10) and higher summer T max even reduced greenness by 2.6% K −1 ( P 0.05). The stimulating effects of increasing T min were likely caused by reduced low temperature constraints, and the apparent negative effects of higher T max on greenness were probably due to the accompanying decline in water availability. The dominant enhancing effect of nighttime warming indicates that climatic warming will probably have stronger impact on TP ecosystems than on apparently similar Arctic ecosystems where vegetation is controlled mainly by T max . Our results are crucial for future improvements of dynamic vegetation models embedded in the Earth System Models which are being used to describe the behavior of the Asian monsoon. The results are significant because the state of the vegetation on the TP plays an important role in steering the monsoon.

Mobilization and transport of metal-rich colloidal particles from mine tailings into soil under transient chemical and physical conditions - Cong Lu; Yaoguo Wu; Sihai Hu; Muhammad Ali Raza; Yilin Fu (Environmental Science and Pollution Research, 2016)

The potential function of prohibitin during spermatogenesis in Chinese fire-bellied newt Cynops orientalis - Jia-Min Jin; Cong-Cong Hou; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

Residue behavior and risk assessment of mixed formulation of imidacloprid and chlorfenapyr in chieh-qua under field conditions - Jian Xiang Huang; Cong Yun Liu; Da Hai Lu; Jia Jia Chen; Yi Cai Deng; Fu Hua Wang (Environmental Monitoring and Assessment, 2015)

The Lhx9 homeobox gene controls pineal gland development and prevents postnatal hydrocephalus - Fumiyoshi Yamazaki; Morten Møller; Cong Fu; Samuel J. Clokie; Artem Zykovich; Steven L. Coon; David C. Klein; Martin F. Rath (Brain Structure and Function, 2015)

Intercropping enhances soil carbon and nitrogen - Wen‐Feng Cong; Ellis Hoffland; Long Li; Johan Six; Jian‐Hao Sun; Xing‐Guo Bao; Fu‐Suo Zhang; Wopke Van Der Werf (Global Change Biology, 2015)
Intercropping, the simultaneous cultivation of multiple crop species in a single field, increases aboveground productivity due to species complementarity. We hypothesized that intercrops may have greater belowground productivity than sole crops, and sequester more soil carbon over time due to greater input of root litter. Here, we demonstrate a divergence in soil organic carbon (C) and nitrogen (N) content over 7 years in a field experiment that compared rotational strip intercrop systems and ordinary crop rotations. Soil organic C content in the top 20 cm was 4% ± 1% greater in intercrops than in sole crops, indicating a difference in C sequestration rate between intercrop and sole crop systems of 184 ± 86 kg C ha −1 yr −1 . Soil organic N content in the top 20 cm was 11% ± 1% greater in intercrops than in sole crops, indicating a difference in N sequestration rate between intercrop and sole crop systems of 45 ± 10 kg N ha −1 yr −1 . Total root biomass in intercrops was on average 23% greater than the average root biomass in sole crops, providing a possible mechanism for the observed divergence in soil C sequestration between sole crop and intercrop systems. A lowering of the soil δ 15 N signature suggested that increased biological N fixation and/or reduced gaseous N losses contributed to the increases in soil N in intercrop rotations with faba bean. Increases in soil N in wheat/maize intercrop pointed to contributions from a broader suite of mechanisms for N retention, e.g., complementary N uptake strategies of the intercropped plant species. Our results indicate that soil C sequestration potential of strip intercropping is similar in magnitude to that of currently recommended management practises to conserve organic matter in soil. Intercropping can contribute to multiple agroecosystem services by increased yield, better soil quality and soil C sequestration.

Phylogenetic analysis of 32 porcine circovirus type 2 isolates from Shandong, China - Jianli Shi; Shaojian Xu; Fang Fu; Xiaoyan Cong; Xiaoyuan Yuan; Zhe Peng; Jiaqiang Wu; Wenbo Sun; Yijun Du; Jun Li; Baohua Huang; Jinbao Wang (Archives of Virology, 2015)

Genetic polymorphism of the 26 short tandem repeat loci in the Chinese Hebei Han population using two commercial forensic kits - Liang Lei; Jie Xu; Qingqing Du; Lihong Fu; Xiaojing Zhang; Feng Yu; Chunling Ma; Bin Cong; Shujin Li (Molecular Biology Reports, 2015)

Isolation and molecular characterization of two novel HMW-GS genes from Chinese wheat (Triticum aestivum L.) landrace Banjiemang - Hui Shao; Tian-hong Liu; Cong-Fu Ran; Li-Qun Li; Jing Yu; Xin Gao; Xue-Jun Li (Genes & Genomics, 2015)

Recent spring phenology shifts in western C entral E urope based on multiscale observations - Yongshuo H. Fu; Shilong Piao; Maarten Op de Beeck; Nan Cong; Hongfang Zhao; Yuan Zhang; Annette Menzel; Ivan A. Janssens (Global Ecology and Biogeography, 2014)
Aim Although numerous studies have reported advanced N orthern H emisphere spring phenology since the 1980s, recent studies based on remote sensing have reported a reversal or deceleration of this trend. This study aimed (1) to fully understand recent spring phenology shifts using both in situ observations and satellite‐based normalized difference vegetation index ( NDVI ) datasets, and (2) to test whether the NDVI methods capture the trends observed in situ. Location W estern C entral E urope. Methods Temporal spring phenology trends (leaf unfolding dates) were examined using 1,001,678 in situ observations of 31 plant species at 3984 stations, as well as NDVI ‐based start‐of‐season dates, obtained using five different methods, across the pixels that included the phenology stations. Results In situ and NDVI observations both indicated that spring phenology significantly advanced during the period 1982–2011 at an average rate of −0.45 days yr −1 . This trend was not uniform across the period and significantly weakened over the period 2000–2011. Furthermore, opposite trends were found between in situ and NDVI observations over the period 2000–2011. Averaged over all species, the in situ observations indicated a slower but still advancing trend for leaf unfolding, whereas the NDVI series showed a delayed spring phenology. Main conclusions The recent trend reversal in the advancement of spring phenology in western C entral E urope is likely to be related to the response of early spring species to the cooling trend in late winter. In contrast, late spring species continued to exhibit advanced leaf unfolding, which is consistent with the warming trend during spring months. Because remote sensing does not distinguish between species, the signal of growing‐season onset may only reflect the phenological dynamics of these earliest species in the pixel, even though most species still exhibit advancing trends.

Screening and monitoring zearalenone-producing Fusarium species by PCR and zearalenone by monoclonal antibodies in feed from China - Shi-Chun Pei; Yu-Ping Zhen; Jian-Wei Gao; Won-Jong Lee; Hong-Fu Zhang; Cheng Ji; Xuan-Zhe Zhang; Cong Chen (Food Additives & Contaminants Part B-Surveillance, 2014)

Development of three X-linked tetrameric microsatellite markers for forensic purposes - Chunnan Dong; Lihong Fu; Xiaojing Zhang; Chunling Ma; Feng Yu; Shujin Li; Bin Cong (Molecular Biology Reports, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Annual input fluxes of heavy metals in agricultural soil of Hainan Island, China - Wei Jiang; Qingye Hou; Zhongfang Yang; Tao Yu; Cong Zhong; Yi Yang; Yangrong Fu (Environmental Science and Pollution Research, 2014)

Tetrabromobisphenol A recovery from computer housing plastic by a new solvothermal process - Cong-Cong Zhang; Veena Sahajwalla; Fu-Shen Zhang (Environmental Chemistry Letters, 2014)

Indole-3-acetic acid reverses the harpin-induced hypersensitive response and alters the expression of hypersensitive-response-related genes in tobacco - Jie Song; Xiao-chong Gong; Wei-guo Miao; Fu-cong Zheng; Cong-feng Song; Ming-hua Wang (Biotechnology Letters, 2014)

Road Detection from Optical Remote Sensing Imagery Using Circular Projection Matching and Tracking Strategy - Gang Fu; Hongrui Zhao; Cong Li; Limei Shi (Journal of the Indian Society of Remote Sensing, 2013)

The UDP glucose: flavonoid-3-O-glucosyltransferase (UFGT) gene regulates anthocyanin biosynthesis in litchi (Litchi chinesis Sonn.) during fruit coloration - Zhi Chang Zhao; Gui Bing Hu; Fu Chu Hu; Hui Cong Wang; Zhuan Ying Yang; Biao Lai (Molecular Biology Reports, 2012)

Pyrosequencing of a short fragment of the amelogenin gene for gender identification - Shujin Li; Ting Feng; Lihong Fu; Zhenhua Li; Chunguang Lou; Xiaojing Zhang; Chunling Ma; Bin Cong (Molecular Biology Reports, 2012)

Comparative full-length sequence analysis of Marek’s disease virus vaccine strain 814 - Feng Zhang; Chang-Jun Liu; Yan-Ping Zhang; Zhi-Jie Li; Ai-Ling Liu; Fu-Hai Yan; Feng Cong; Yun Cheng (Archives of Virology, 2012)

The Community Dynamics of Major Bioleaching Microorganisms During Chalcopyrite Leaching Under the Effect of Organics - Qihou Li; Ye Tian; Xian Fu; Huaqun Yin; Zhijun Zhou; Yiting Liang; Guanzhou Qiu; Jie Liu; Hongwei Liu; Yili Liang; Li Shen; Jing Cong; et al. (Current Microbiology, 2011)

Significant association of SNP rs2106261 in the ZFHX3 gene with atrial fibrillation in a Chinese Han GeneID population - Cong Li; Fan Wang; Yanzong Yang; Fenfen Fu; Chengqi Xu; Lisong Shi; Sisi Li; Yunlong Xia; Gang Wu; Xiang Cheng; Hui Liu; Chuchu Wang; et al. (Human Genetics, 2011)

Supplementary data: Assessment of genetic diversity ofLycoris longituba (Amaryllidaceae) detected by RAPDs - Chuan-Liang Deng; Jian Zhou; Wu-Jun Gao; Fu-Cong Sun; Rui-Yun Qin; Long-Dou Lu (Journal of Genetics, 2006)